Partial duplication 4q in a newborn caused by rearrangement der (20),t(4;20)(q21;q13.1)mat - Talavera-Vargas-Machuca, Sergio (2016)
duplicación 4q,We report the case of a newborn with multiple congenital malformations by unbalanced chromosome complement 46,XY,der(20),t(4;20)(q21;q13.1)mat originated by a reciprocal translocation apparently balanced between chromosomes 4 and 20 in the mother who had a karyotype 46,XX,t(4;20)(q21;q13.1) de novo. The proband´s karyotype showed a duplication of the distal segment of the long arm of chromosome 4 (partial trisomy 4q). The phenotype was altered, presenting several craniofacial, and malformations of internal organs that led to his early death. hereditary commitment and to detect posible carriers. The risks also were determined to provide an appropiate genetic counseling.